Studi Penyebaran dan Peran Kegiatan Industri dalam Peningkatan Pendapatan Asli Daerah Kabupaten Sumedang - Santi Latifah; Supratignyo Aji (Program Studi Perencanaan Wilayah dan Kota Universitas Pasundan, 2015)
This research was done in an effort to determine the role of industrial activity in increasing local revenues Sumedang Regency. The approach taken in this study by analyzing the spread and development of industrial activities, the impact of industrial activities in increasing local revenues as well as determine the role of each district in an increase in revenue. The results of the analysis proved that industrial activity has been found to increase local revenues of Sumedang Regency. Industrial activity has a role in helping to increase revenue Sumedang Regency seen from the share of the industry, industrial production and population. Each of these variables contribute different. To share industry if the value share of small industries, it can encourage increased local revenues, but on the contrary if the value is greater then the industry share of local revenues would be relatively small. As for industrial production and the number of people if the value of industrial production and the large population increase local revenue, but on the contrary if the industrial production and the small population of the original income are relatively small region.